Implementing Berau Folklore into English Learning: Fostering Students’ Reading Skills and Local Wisdom Awareness - Rahmiwati, Rahmiwati; Januarius Mujiiyanto; Hendi Pratama (English Education Journal, 2024)
As educators, lecturers should integrate sufficient reading materials that could foster not only students’ reading comprehension, critical thinking, or vocabulary mastery, but also local wisdom awareness. Thus, this research focuses on integrating local wisdom, Berau Folklore, into English learning. Specifically, this research aims to: (1) describe the planning stage for using Berau folklore to enhance student’s awareness about local wisdom, (2) explain its use in English practice and media preparation, (3) explain the assessment process, and (4) evaluate its effectiveness as reading material. This study employs exploratory sequential mixed method design. The instruments used were interview, classroom observation, document analysis, and tests. The interview was constructed based on the theory of Bamford and Day (2004) whereas the observation was adopted and modified from Ferdila (2014). The pre-test and post-test were given to 15 tertiary students at STITM Tanjung Redeb, Berau who took the Extensive Reading class. The implementation of Berau folklore into reading class, involved the stages of pre-reading, while-reading, and post-reading. However, the tests scores indicate that the use of Berau Folklore is considered ineffective as reading materials for tertiary students. Particularly, it did not significantly increase students’ vocabulary. Thus, this study can be a reference for further researchers to find and employ another learning material other than folklore to foster students’ vocabulary mastery and cultural awareness.